2017
DOI: 10.1037/fam0000277
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional capital during the early years of marriage: Why everyday moments matter.

Abstract: Throughout a marriage couples will share countless ordinary moments together that may seem trivial, but which actually have potential to affirm and strengthen relational bonds. According to theories of emotional capital, the accumulation of shared positive moments in a relationship should serve as an essential resource for protecting the relationship against threats. To date, however, few empirical studies have explored the role emotional capital may play in shaping responses to negative relationship experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…First, the fact that it has taken this long to recognize the overall stability of marital satisfaction implies that the field has not devoted sufficient attention to describing how marriages change. The welcome progress of the past 10 years continues a decades‐long trend toward gathering more detailed data from married couples, moving beyond cross‐sectional snapshots to exploit the potential of multiwave longitudinal designs and experience sampling methods (e.g., Walsh, Neff, & Gleason, ). Psychometrically sound and theoretically coherent instruments for assessing marital satisfaction are in wide use (e.g., Funk & Rogge, ).…”
Section: Trajectories Of Marital Satisfactionmentioning
confidence: 99%
“…First, the fact that it has taken this long to recognize the overall stability of marital satisfaction implies that the field has not devoted sufficient attention to describing how marriages change. The welcome progress of the past 10 years continues a decades‐long trend toward gathering more detailed data from married couples, moving beyond cross‐sectional snapshots to exploit the potential of multiwave longitudinal designs and experience sampling methods (e.g., Walsh, Neff, & Gleason, ). Psychometrically sound and theoretically coherent instruments for assessing marital satisfaction are in wide use (e.g., Funk & Rogge, ).…”
Section: Trajectories Of Marital Satisfactionmentioning
confidence: 99%
“…Similarly, distressed dyads undergoing couples' therapy reported greater relationship satisfaction post‐therapy when partners reported providing greater capitalization support (path E; Hershenberg et al, ). In a daily diary study, Walsh and colleagues found that on days of greater relationship threat, couples who had accumulated more positive moments (some of which may have included capitalizing on good news) with their partners maintained relationship satisfaction levels compared to couples with fewer positive moments (Walsh, Neff, & Gleason, ). Thus, capitalization may help couples remain positive in the face of threat and build emotional capital during stressful times (Feeney & Lemay, ).…”
Section: Interpersonal Outcomes For Relationshipsmentioning
confidence: 99%
“…Theoretical models suggest that greater sexual well-being might be a protective factor for lower stress (theory of emotional capital; Feeney & Lemay, 2012) and that poorer sexual well-being may be a risk factor for heightened stress (transactional model of stress; Lazarus & Folkman, 1984). The theory of emotional capital (Feeney & Lemay, 2012) suggests that partners who accumulate greater “emotional capital”—a series of positive, emotionally shared experiences, such as positive sexual interactions—are less reactive to relationship stressors and threats than couples with lower emotional capital (Walsh, Neff, & Gleason, 2016). Thus, couples with greater sexual well-being in the transition to parenthood might be more protected against the experience of stress.…”
Section: Sexual Well-being and Stressmentioning
confidence: 99%